Immunohistochemical spectrum of lymphoma in Patan Hospital: a two-year retrospective study - Maharjan, Anju; Maharjan, Nayan; Khadgi, Rohit; Shrestha, Girishma; Rajbhandari, Aasiya; Shrestha, Manisha; Shah, Prakriti; Sayami, Pratik; Gautam, Dipti (Journal of Pathology of Nepal, 2025)
Background: Lymphomas are a heterogeneous group of disorders arising from lymphoid tissue and are categorized based on histological and immunophenotypical features. Accurate subclassification of lymphoma is essential for appropriate management and prognostication.  This study aimed to analyze the distribution of lymphoma cases at Patan Hospital using immunohistochemistry and to categorize their subtypes according to the 2017 WHO classification system.Materials and Methods: This retrospective cross-sectional study was conducted in the Department of Pathology, Patan Hospital, from July 2023 to July 2025. All lymphoma cases with complete immunohistochemical evaluation were included. Cases were classified according to the 2017 WHO classification system.Results: A total of 51 cases were analyzed, with patients ranging from 7 to 92 years of age and a male-to-female ratio of 2:1. Non-Hodgkin lymphoma accounted for 92.2% of cases, predominantly B-cell lymphomas (87.2%). Diffuse Large B Cell Lymphoma was the most common subtype (56.1%). T-cell lymphomas constituted 12.8% of Non Hodgkin Lymphoma. Nearly equal extranodal (51%) and nodal (49%) involvement was observed. The gastrointestinal tract and cervical lymph nodes were the most common extranodal and nodal sites respectively. Hodgkin lymphoma accounted for 7.8% of cases, all of which were of the classic type.Conclusions: Diffuse large B-cell lymphoma was the most commonly diagnosed lymphoma at Patan Hospital, with B-cell non-Hodgkin lymphomas representing the majority of cases. Immunohistochemistry was essential for accurate subclassification and prognostic assessment, providing valuable baseline data for future regional studies.